Guided faith and leadership development in Risale-I Nuur - Mohammad Tolba Said, Mohammad; Umachandran, Krishnan; Abd Rashid, Adnan (Centre For Human and Community Well-Being Faculty of Islamic Studies The National University Of Malaysia, 2018)
Bediuzzaman Said Nursi’s interpretations of the religion lead to a cogent writing of the masterpiece Risale-i Nur. It guides and enlightens the people to be cautious on the use of freedom and its protection with clear definition on the liberty limits. It has identified that permission or approval of unlawful maltreatment proved as hurdle to progress. The Risale-i Nur validates that all lives, on all levels, are interrelated. interconnected and interdependent, like concentric or intersecting circles. Development is never wavered and uncompromised with misery, dishonesty, hostility, disdained fraternity, cruelty, and greed. Pillars of Faith cannot be erected on shear imagination, but can challenge the universe by showing care, tolerance, and honesty. Heart disposition and sensation cannot be captured in any real form other than through displayed quality of humanity. Cultural ability should elegantly handle errors, attempts and failures, humbly confirms the validity of leadership with no arrogance thereby evolving a prominent community originated on a communal moral charter that comprises reverence and attention for the public veracity, rights, economic justice, and peace. The absence of integrity in the modern material architype is the motive for the chaotic transformations carried out by explanations of science and technology, understood as the key drivers to failing environmental obliteration. Islam aids as an incredible force to defend human self-respect, provide assurance and maintain world peace. Risale-i Nur authenticates that all lives at all levels, are interrelated. interconnected and interdependent, like concentric or intersecting circles; while materialistic development is always compromised with misery, dishonesty, hostility, disdained fraternity, cruelty, and greed.